Gaze-directed gameplay in first person computer games - Antunes, João Eiras (2017)
The use of eye tracking systems in computer games is still at an early stage. Commercial eye trackers and researches have been focusing in gaze-oriented gameplay as an alternative to traditional input devices. This dissertation proposes to investigate the advantages and disadvantages of the use of these systems in computer games. For it, instead of using eye tracking as a simple direct control input, it is proposed to use it in order to control the attention of the player’s avatar (e.g., if the player notices an obstacle in the way, the avatar will notice it too and avoid it) and the game’s procedural content generation (e.g., spawn obstacles in the opposite side of the screen to where the player’s attention is focused). To demonstrate the value of this proposal, it was developed and is herein presented the first-person shooter "Zombie Runner". Tests showed that the implementation meets the stipulated technical requirements and that, although it still needs improvements in terms of precision and robustness, eye tracking technology can be successfully used to to make the player experience more immersive and challenging.